sj-pptx-2-tag-10.1177_17562848221124029 – Supplemental material for ‘FLARE’ of tumor marker in advanced gastric cancer treated with first-line systemic therapy - Fangyuan Zhang; Menglan Zhai; Jinru Yang; Lei Zhao; Zhenyu Lin; Jing Wang; Tao Zhang; Dandan Yu (SAGE Journals, 2022)
Supplemental material, sj-pptx-2-tag-10.1177_17562848221124029 for ‘FLARE’ of tumor marker in advanced gastric cancer treated with first-line systemic therapy by Fangyuan Zhang, Menglan Zhai, Jinru Yang, Lei Zhao, Zhenyu Lin, Jing Wang, Tao Zhang and Dandan Yu in Therapeutic Advances in Gastroenterology
Keywords: Nutrition and Dietetics not elsewhere classified; Oncology and Carcinogenesis not elsewhere classified; Pharmacology and Pharmaceutical Sciences not elsewhere classified